2021
DOI: 10.7759/cureus.13646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant Tricuspid Annuloplasty on Early Outcomes of Mitral Valve Replacement: A Study on Rheumatic Heart Disease Patients

Abstract: Introduction Mitral valve abnormalities in rheumatic heart disease commonly lead to functional tricuspid regurgitation. Tricuspid annuloplasty (TA) is often performed in these cases along with mitral valve replacement (MVR). Our aim was to compare the perioperative morbidity and mortality among those patients that underwent mitral valve replacement with tricuspid annuloplasty versus those that underwent isolated mitral valve replacement. Methods A retrospective analysis of 158 patients that underwent mitral va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 24 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…The cumulative incidence of death in Arafat et al series at 7 years was 4.8% (10). Similar studies were conducted by Farooq and Bernal and their colleagues in younger patients at a mean age of 41-46 years, the 30-day mortality was 4.5 -5.9% (11,12). The Kaplan-Meier survival probability in the series of Bernal and colleagues was 74.4% at 10 years and age >65 years was the only predictor of late mortality (12).…”
supporting
confidence: 71%
See 4 more Smart Citations
“…The cumulative incidence of death in Arafat et al series at 7 years was 4.8% (10). Similar studies were conducted by Farooq and Bernal and their colleagues in younger patients at a mean age of 41-46 years, the 30-day mortality was 4.5 -5.9% (11,12). The Kaplan-Meier survival probability in the series of Bernal and colleagues was 74.4% at 10 years and age >65 years was the only predictor of late mortality (12).…”
supporting
confidence: 71%
“…In a similar study by Farooq and colleagues on TA plus mitral valve replacement there was no progression of TR reported at three years (11). Recently reported randomized controlled trial by Gammie and colleagues showed much lesser progression of moderate TR at two years (0.6% vs. 6.1% control group, relative risk, 0.09; 95% CI, 0.01 to 0.69) (3).…”
mentioning
confidence: 89%
See 3 more Smart Citations